NEGOTIATING BTS’ SOFT MASCULINITY IN A MALAY-ISLAMIC CONTEXT - Suryani; Dedes Wirdana (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Local identities and global symbols have been strengthened by globalization, which has encouraged popular cultural exchanges between countries, including through the Korean Wave (Hallyu) with BTS as the main icon. BTS represents soft masculinity through feminine aesthetics, emotional expression, and empathetic communication. Although it has been widely studied globally, there is still a lack of research that highlights the perception of BTS masculinity in the context of Malay-Islamic culture in Bangka.This research aims to explore how ARMY Institut Pahlawan 12 interprets BTS masculinity, especially in negotiations between local values and global cultural influences. The method used is qualitative descriptive with in-depth interview techniques, documentation, and literature study. Informants are purposively selected from among active ARMYs. The results show that BTS is understood as a masculine figure despite adopting feminine attributes. This perception is formed through three stages: selection (initial exposure to music and performance), interpretation (meaning of lyrics and attitudes), and reaction (active support and imitation of style). ARMYs demonstrate a selective acceptance that reflects a hybrid identity, combining local values such as politeness and honor with a flexible and reflective global expression. This study contributes to gender studies in Indonesia and forms the basis for inclusive communication strategies in character education and popular culture.